Acetylcholinesterase Inhibitors Promote Angiogenesis in Chick Chorioallantoic Membrane and Inhibit Apoptosis of Endothelial Cells. (16th September 2013) - Mortazavian, Seyed Mohsen; Parsaee, Heydar; Mousavi, Seyed Hadi; Tayarani-Najaran, Zahra; Ghorbani, Ahmad; Sadeghnia, Hamid Reza
Abstract : Alzheimer's disease (AD) is one of the most common causes of dementia in the elderly. Recently, a great attention has been paid to the possible role of vascular changes in the pathogenesis of AD. Reduced microvascular density and degeneration of the endothelium are of structural cerebrovascular changes in AD. Acetylcholinesterase (AChE) inhibitors are widely used for the improvement of AD symptoms. Until now, however, the effects of AChE inhibitors on vascular changes including angiogenesis and endothelial cell apoptosis are not fully understood. In the present work, the effects of three AChE inhibitors (donepezil, rivastigmine, and galantamine) were tested on H2 O2 -induced apoptosis in human umbilical vein endothelial cells (HUVECs) and on angiogenesis in chicken chorioallantoic membrane model. Incubation of HUVEC with H2 O2 led to a significant decrease in cell viability and an increase in the percentage of apoptotic cells. The tested drugs, at concentrations of 1–100  μ M, significantly inhibited the H2 O2 -induced toxicity. Also, all donepezil, rivastigmine and galantamine significantly increased the number of vessels in the chorioallantoic membrane when injected into fertilized eggs. In conclusion, AChE inhibitors possess angiogenesis-accelerating properties and have antiapoptotic effects on endothelial cells. These effects of AChE inhibitors may be involved in their beneficial effects on AD.